Beneficial performance of a quasi-zero stiffness vibration isolator with generalized geometric nonlinear damping. (March 2021) - Cheng, Chun; Ma, Ran; Hu, Yan
Generalized geometric nonlinear damping based on the viscous damper with a non-negative velocity exponent is proposed to improve the isolation performance of a quasi-zero stiffness (QZS) vibration isolator in this paper. Firstly, the generalized geometric nonlinear damping characteristic is derived. Then, the amplitude-frequency responses of the QZS vibration isolator under force and base excitations are obtained, respectively, using the averaging method. Parametric analysis of the force and displacement transmissibility is conducted subsequently. At last, two phenomena are explained from the viewpoint of the equivalent damping ratio. The results show that decreasing the velocity exponent of the horizontal damper is beneficial to reduce the force transmissibility in the resonant region. For the case of base excitation, it is beneficial to select a smaller velocity exponent only when the nonlinear damping ratio is relatively large.